Evaluación de la producción forrajera y calidad nutricional de Brachiaria brizantha con fertilización química, orgánica y micorrizas, en la parroquia Valladolid, provincia de Zamora Chinchipe - Toledo Calva, Davidson Salatiel (2023)
Cattle raising is a fundamental support for Ecuador's agricultural sector due to its dynamism in the rural economy; pastures represent the most important source of livestock feed and are low cost. The limited yield and low nutritional value of pastures is a preponderant factor in the decision making of the farmer to improve or implement new alternatives with potential forage species. Brachiaria brizantha is a species that is being cultivated on a larger scale in the study area; however, to increase production it is necessary to implement management practices, including the management of fertilization in pastures, which is generally null or limited. The present study evaluated the forage production and nutritional quality of Brachiaria brizantha with chemical, organic and mycorrhizal fertilization. The trial was established in Valladolid parish, under a Completely Randomized Block Design (CRBD) with 4 treatments and 3 replications. T1 (control), T2 (chemical fertilizer), T3 (organic fertilizer) and T4 (mycorrhizae). The variables height, diameter, number of leaves, number of tillers were recorded every 8 days from germination, green matter and dry matter production were evaluated at 106 days after sowing (DDS), as well as the nutritional variables. Statistical analyses ANOVA and LSD Fisher's comparison test were performed in the InfoStat program. The grass reached the highest height 107.56 cm with T2 and the lowest 93.85 cm with T4 at 106 DDS. The best MV production was obtained with chemical fertilization 99 166.67 kg. ha-1 per cutting, as was DM production with 11 571.11 kg. ha-1. The highest ash content was obtained with T4 (15.74 %), while crude protein (CP) was obtained with T2 (16.79 %). The yield variables did not show statistically significant differences, but in general the T2 was predominant and in relation to the highest content in nutritional value were T2 and T4. Keywords: Poaceae, fertilizers, yield, nutritional value, protein.